2013
DOI: 10.1523/jneurosci.5661-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Increased PTEN Nuclear Translocation in Excitotoxic and Ischemic Neuronal Injuries

Abstract: Stroke is the leading cause of disability in developed countries. However, no treatment is available beyond 3 h post-ictus. Here, we report that nuclear translocation of PTEN (phosphatase and tensin homolog deleted on chromosome TEN) is a delayed step causatively leading to excitotoxic (in vitro) and ischemic (in vivo) neuronal injuries. We found that excitotoxic stimulation of N-methyl-D-aspartate (NMDA) resulted in PTEN nuclear translocation in cultured neurons, a process requiring mono-ubiquitination at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 63 publications
4
72
1
Order By: Relevance
“…Consistent with these previous results, we also demonstrated that inhibiting the nuclear translocation of PTEN using a peptide designed to block the K13/K289-ubiquitination of PTEN exhibits neuroprotective effects (Zhang et al, 2013a), emphasizing the role of nuclear PTEN in neuronal degeneration. As nuclear PTEN accumulation appears to be LMC-MN-exclusive in mir-17$92 MND embryos and as LMCMNs are the most vulnerable MN subtype to degenerate in patients with ALS (Kanning et al, 2010;Kaplan et al, 2014), this raises the possibility that an intrinsic MN subtype modifier, such as PTEN, might contribute to the vulnerability of limbinnervating MNs in ALS (Kaplan et al, 2014).…”
Section: Intrinsic and Extrinsic Mn Survival Controlsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with these previous results, we also demonstrated that inhibiting the nuclear translocation of PTEN using a peptide designed to block the K13/K289-ubiquitination of PTEN exhibits neuroprotective effects (Zhang et al, 2013a), emphasizing the role of nuclear PTEN in neuronal degeneration. As nuclear PTEN accumulation appears to be LMC-MN-exclusive in mir-17$92 MND embryos and as LMCMNs are the most vulnerable MN subtype to degenerate in patients with ALS (Kanning et al, 2010;Kaplan et al, 2014), this raises the possibility that an intrinsic MN subtype modifier, such as PTEN, might contribute to the vulnerability of limbinnervating MNs in ALS (Kaplan et al, 2014).…”
Section: Intrinsic and Extrinsic Mn Survival Controlsupporting
confidence: 91%
“…In addition to the role of nuclear PTEN in LMC-MNs uncovered in this study, PTEN has also been found to translocate into the nucleus in response to neuronal injuries such as ischemia, traumatic brain injury, and N-methyl-D-aspartateinduced excitotoxicity (Goh et al, 2014;Howitt et al, 2012;Zhang et al, 2013a). Consistent with these previous results, we also demonstrated that inhibiting the nuclear translocation of PTEN using a peptide designed to block the K13/K289-ubiquitination of PTEN exhibits neuroprotective effects (Zhang et al, 2013a), emphasizing the role of nuclear PTEN in neuronal degeneration.…”
Section: Intrinsic and Extrinsic Mn Survival Controlmentioning
confidence: 64%
“…Recently, an intriguing study by Zhang et al demonstrated that nuclear translocation of PTEN might be a step causatively leading to excitotoxic ( in vitro ) and ischemic ( in vivo ) neuronal loss (50). Since PTEN deletion impact both neuronal survival and axon regeneration, it would be interesting to assess the contribution of nuclear vs cytosolic PTEN after axotomy.…”
Section: Mtor As An Indicator Of Regenerative Competence?mentioning
confidence: 99%
“…PTEN can induce neuronal damage after ischemic insults through several pathways (Figure 3): antagonizing the phosphatidylinositol-3 kinase (PI3K) signaling pathway, 62 negatively regulating the membrane expression and function of GABAA receptors (GABA A Rs), 63 positively regulating extrasynaptic NMdARs 64 and interfering with nuclear signaling. 65 However, PTEN also induces a neuroprotective effect through activating the GluN2A cell prosurvival pathway. 64 Although it has a neuroprotective effect, the main action of PTEN is to promote neuronal death after stroke.…”
Section: Glun2b-pten Signaling Pathwaymentioning
confidence: 99%
“…66,67 Zhang et al 65 demonstrated that the application of Tat-K13, a peptide that prevents the nuclear translocation of PTEN, even 6 hours after stroke strongly protected against ischemic brain damage. Although delayed administration of a PTEN inhibitor bp as long as 24 hours after ischemia did not reduce infarction during the acute phase, functional recovery was improved.…”
Section: Glun2b-pten Signaling Pathwaymentioning
confidence: 99%